Analisis Treatment Planning System dengan Menggunakan Teknik Box dan Teknik Antero Posterior-Postero Anterior pada Kasus Kanker Serviks - Yasinta Erikania Daniartie; Pratiwi Sri Wardani; Devina Rayzy Perwitasari Sutaji Putri; Robert Janssen Stevenly; Suryaningsih Suryaningsih (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2022)
Cervical cancer is cancer that grows in the cells on the cervix. Cervical cancer can be treated using radiotherapy. The purpose of this study was to determine the ratio of the dose received by the target volume and Organ at Risk (OAR) as well as the isodose curve using 4 directions of radiation field (gantry angle: 0°, 90°, 180° and 270°) and 2 directions of radiation field (gantry angle: 0° and 180°). The data processing step in this research was to do radiation planning (planning) by using 4 directions of radiation field (gantry angle: 0°, 90°, 180° and 270°) and 2 directions of radiation field (gantry angle: 0° and 180°). Then a comparative analysis of the dose value received by the target volume and Organ at Risk (OAR) was carried out. A comparative analysis of the isodose curve was performed by using each of the techniques. The results obtained from this study are the target volume has minimal dose using the box technique compared to the antero posterior-postero anterior technique. For Organ at Risk, namely bladder and rectum, the dose was minimal by using the box technique compared to using the anteroposteriorpostero anterior technique. Meanwhile, the right and left femoral heads received higher doses using the box technique than the antero-posterior-postero anterior technique. And for the isodose curve planning results using the box technique shows a more even distribution of the dose distribution to the entire target volume compared to the antero posterior-postero anterior technique.